SOME OBSERVATIONS ON THE CONCEPT OF ANALYTIC FOLIATION - Benazic Tomé, Renato Mario (2009)
In the first part of this paper we give three definitions equivalent of theconcept of k-dimensional foliation on a complex analytic manifold. Below, we provideone quarter equivalent definition for foliations of dimension one, using the concept of holomorphic vector field.